Uma teoria política da ação: uma defesa da ideia de justificação pública do liberalismo político de John Rawls - Yago Condé Ubaldo de Carvalho (2022)
This work addresses Gerald Gaus's critique of liberal theories that, despite considering the problem of public justification as a matter of first importance, do not offer satisfactory bases to support their approaches – in particular, they do not start from a solid understanding of the very concept of justification, a matter which the author tries to remedy by building an epistemological approach. To offer an answer to this criticism, I develop an interpretation of John Rawls's theory of justice that highlights the role of a conception of the person and practical rationality and how they lead to his idea of publica reason, so that Political Liberalism may be reconstructed as a political theory of action. This reading is intended to show that the author's approach to public justification has more solid foundations than initially conceived, and stems from a fundamental methodological position on the relationship between political philosophy and epistemology and other fields of knowledge.